Thoracic sympathectomy for hyperhidrosis with and without botulinum toxin injection - Rezk Abu-Gamila; Elkahely Mohamed; Abdallah Nosair (Wolters Kluwer Medknow Publications, 2019)
Background and aims Primary hyperhidrosis is a disorder of excessive sweating of unknown etiology, associated with emotional, psychological, and educational problems. This study described our experience in managing hyperhidrosis via endoscopic thoracic sympathectomy (ETS) with and without intradermal botulinum toxin type A (BTX-A) injections. Patients and methods This retrospective study included 50 patients treated by ETS with either BTX-A (20 patients) or not (ETS only; 30 patients) in security forces hospital, Saudi Arabia, between January 2014 and February 2017. Information was obtained from computerized medical records and a telephone survey about postoperative complications. Results A total of 50 patients were operated and included in this study. The mean age was 23.55±6.12 years. The majority (70%) had axillary and palmar hyperhidrosis and 30% had palmar hyperhidrosis. In ETS, surgical technique was done at T2-T3 level in 56% of patients. Mean ETS procedure time was 39.6±14.29 min, with no conversion. Mean hospital stay was 1.5±0.85 days. Success rates of ETS in patients with axillary and palmar were 95 and 96.7%, respectively, whereas success rates of BTX-A+ETS in patients with axillary and palmar were 100 and 100%, respectively. Compensatory sweating was recorded in 20% among every group, with minimal other postoperative and postinjection complications being recorded, with no significant difference between studied groups (P=0.316). Conclusion BTX-A injection followed by ETS is safer and effective and has minimal postoperative complications.